Anime and Japanese: potential improvement of teaching meth- ods on the basis of preliminary survey - Akhapov Y.A.; Baubekkyzy Z. (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы)
Japanese anime and manga is considered as an integral part of Japa- nese popular culture. In recent years, it began to spread widely throughout